2023
DOI: 10.1073/pnas.2207831120
|View full text |Cite
|
Sign up to set email alerts
|

Propofol disrupts alpha dynamics in functionally distinct thalamocortical networks during loss of consciousness

Abstract: During propofol-induced general anesthesia, alpha rhythms measured using electroencephalography undergo a striking shift from posterior to anterior, termed anteriorization, where the ubiquitous waking alpha is lost and a frontal alpha emerges. The functional significance of alpha anteriorization and the precise brain regions contributing to the phenomenon are a mystery. While posterior alpha is thought to be generated by thalamocortical circuits connecting nuclei of the sensory thalamus with their cortical par… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 69 publications
2
10
0
Order By: Relevance
“…It has been shown that when recording brain activity from the human scalp, the dominant frequencies are in the alpha and beta ranges, which span from 8 to 12 Hz and 13 to 30 Hz, respectively ( Pfurtscheller and Lopes Da Silva, 1999 ; Kilavik et al, 2013 ; Piai et al, 2015 ; Nyhus, 2018 ; Griffiths et al, 2019 ; Barone and Rossiter, 2021 ). Intracranial recordings have demonstrated that alpha oscillations, generated through cortical and thalamocortical mechanisms ( Pfurtscheller and Lopes Da Silva, 1999 ; Weiner et al, 2023 ), are observable in parietal, visual, motor, and auditory cortices. Synchronized alpha-band oscillations have been observed during mental inactivity, often described as an “idling system” ( Pfurtscheller and Lopes Da Silva, 1999 ; Buzsáki and Draguhn, 2004 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that when recording brain activity from the human scalp, the dominant frequencies are in the alpha and beta ranges, which span from 8 to 12 Hz and 13 to 30 Hz, respectively ( Pfurtscheller and Lopes Da Silva, 1999 ; Kilavik et al, 2013 ; Piai et al, 2015 ; Nyhus, 2018 ; Griffiths et al, 2019 ; Barone and Rossiter, 2021 ). Intracranial recordings have demonstrated that alpha oscillations, generated through cortical and thalamocortical mechanisms ( Pfurtscheller and Lopes Da Silva, 1999 ; Weiner et al, 2023 ), are observable in parietal, visual, motor, and auditory cortices. Synchronized alpha-band oscillations have been observed during mental inactivity, often described as an “idling system” ( Pfurtscheller and Lopes Da Silva, 1999 ; Buzsáki and Draguhn, 2004 ).…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the source-to-sensor mixing complicates the interpretation of the topographies generated by signal processing tools that treat each channel individually [6]. In a nonparametric frequency-domain approach, the only way to discover this spatially-correlated structure across sensors is to perform eigenvalue analysis on the cross-spectral density on a frequency by frequency basis, also known as global coherence analysis [48, 57, 58]. If the eigenvalue distribution exhibits sufficient skewness, the associated frequency is deemed coherent and the leading eigenvectors are identified as the ‘principal’ sensor networks at that frequency; in other words a proxy for a strong oscillatory component.…”
Section: Discussionmentioning
confidence: 99%
“…During anesthesia, we found that the alpha power in elderly patients decreased more than other frequencies, which is consistent with the previously reported decrease of spectral power within alpha frequencies in older populations [ 5 ]. Alpha power is generated within thalamocortical circuits [ 26 ]. Cortical development during typical aging follows a ‘last to develop, first to degenerate’ pattern, which means that brain regions with high postnatal area expansion also show the most significant declines in early aging [ 27 ].…”
Section: Discussionmentioning
confidence: 99%